Responses of Chukrasia tabularis seedling growth and physiological characteristics to drought stress - Hongting QUAN; Jieyi ZHU; Fengling LONG; Qian ZHAO; Daoming WU; Shucai ZENG (Huanan Nongye Daxue xuebao)
ObjectiveTo investigate the effects of drought stress on the growth and physiological characteristics of Chukrasia tabularis, and reveal the physiological response mechanism of C. tabularis seedlings to adapt to drought environments.MethodTaking half-year-old C. tabularis seedlings as the research subjects, four treatments were set up: Light drought (65%−70% of field water capacity), moderate drought (50%−55% of field water capacity), severe drought (35%−40% of field water capacity), and control (80%−85% of field water capacity). The growth indicators, photosynthetic parameters, and physiological characteristics of C. tabularis seedlings were measured.ResultModerate and severe drought significantly reduced the plant height growth, leaf width, leaf length and leaf area of C. tabularis seedlings (P<0.05), while light drought promoted root growth. The root length (1103.24 cm) and root volume (2.53 cm3) were significantly higher than those of the control (P<0.05). With the increase of stress intensity, the net photosynthetic rate, stomatal conductance, intercellular CO2 concentration, transpiration rate, and chlorophyll content of C. tabularis seedlings all showed a trend of first increasing and then decreasing, reaching the maximum values under light drought. The proline content reached the maximum value under severe drought, significantly higher than that in the control (P<0.05). The contents of soluble protein and malondialdehyde (MDA), as well as the activities of peroxidase (POD) and superoxide dismutase (SOD) in all drought treatment groups were not significantly different from those in the control.ConclusionA field water capacity of 65%−70% facilitates root growth, biomass accumulation, and enhances photosynthetic efficiency in C. tabularis seedlings, indicating that appropriate drought is generally advantageous for the growth of C. tabularis seedlings.